2016
DOI: 10.5455/ijmsph.2016.09102015176
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip strength as determinant of upper body strength/physical fitness: a comparative study among individuals performing gymnastics (ring athletes) and gymnasium (powerlifters)

Abstract: Background:This study was conducted on two different exercising groups, that is, gymnasium (powerlifters) and gymnastics (ring users). Although the type of physical activity is different, but both of the groups require stamina and coordination of central nervous system and skeletal muscles. In the two groups, the muscle strength of the upper body is remarkable and the handgrip has to be effectual for holding rings (gymnastics) and weights (gymnasium). Also, the time for which the grip can be maintained, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 8 publications
(9 reference statements)
2
21
1
1
Order By: Relevance
“…The comparatively high HGS scores of the current study participants were likely predictable as they are consistent with previous research regarding gymnasts and barbell athletes (Fry et al, 2006;Schoffstall et al, 2010;Ruprai). This may suggest that CF is likely a good system for improving HGS, and therefore useful for general health and fitness.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The comparatively high HGS scores of the current study participants were likely predictable as they are consistent with previous research regarding gymnasts and barbell athletes (Fry et al, 2006;Schoffstall et al, 2010;Ruprai). This may suggest that CF is likely a good system for improving HGS, and therefore useful for general health and fitness.…”
Section: Discussionsupporting
confidence: 89%
“…If these two participants were removed from the data set, 77% of the CF participants in the current study would have demonstrated HGS above normative reference 50th percentiles (Wang et al, 2018). Several studies have established correlations between HGS and barbell athletes as well as gymnastics athletes (Ruprai et al, 2016;Schoffstall et al, 2010;Fry et al, 2006). High HGS values could be expected from this population because of the significant amount of time spent manipulating barbells and other weighted implements in their regular CF training, as well as time spent manipulating their own bodyweight around bars and rings.…”
Section: Discussionmentioning
confidence: 85%
“…21 The positive effect of physical activities on hand grip strength and the weight training of muscle increases their efficiency due to more acquisition of strength and development in adolescents. 22 Thus, it is also evident from this study that the mean grip strengths of the dominant and the non-dominant hand is also increasing gradually as the age group increases.…”
Section: Discussionsupporting
confidence: 59%
“…Firstly, the increase in handgrip strength as the root of initial episode of better hand function because the grip strength reflects the strength generated by the contraction of the various arm and hand muscles involved in the proper functioning of the hand. This is because there is a consensus that handgrip strength is a determinant of hand function and is commonly used to evaluate functional limitation of the hand (Ruprai et al, 2015;Smith et al, 2006). Secondly, the positive impact of ST programme on both the intrinsic and extrinsic muscles of the hand and forearm which enhance both grip and pinch strength and thus, enable the hand to function smoothly could also explain the better hand function observed in this study.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Conjointly with the brain, the hand is the most important organ for accomplishing tasks of adaptation, exploration, prehension, precision, perception, and manipulation, unique to humans (Chao, An, Conney, & Linscheid, 1989). According to Ruprai, Tajpuriya, and Mishra (2015), grip strength and pinch powers are good predictors of total muscular strength and endurance and are important parameters of hand function. The grip and pinch strength measurements are commonly used to evaluate the integrated performances of hand muscles by determining maximal grip and pinch forces that could be produced in one muscular contraction.…”
Section: Introductionmentioning
confidence: 99%